Skuteczność konwencji MOP w polskim . prawie pracy - Chobot, Andrzej (Wydział Prawa i Administracji UAM, 1983)
The study elaborates a problem of relation of the ILO conventions to the internal labour law in Poland having in view general transformations in -the modern world resulting in abandoning extreme dualistic ideas in favor of concepts which are intermediate between monism and dualism in solving the international and internal law relation dilemma. Lack of an explicit regulation of that question in the Polish constitution and a lack of labour code provisions on its relation to the international labour laws as well as a particularly compound nature of problems involved render a discussional and issue stating character of this study. A comparison of basic principles of labour law in Poland with relevantly ordered conventions of the ILO proves a high degree of their interference. The conventions are also analogous to the Polish law within the framework of respective principles. Since the basic principles of internal law are developed not only internally but also externally, outside of State, in the ILO conventions, the latter should perform, among others, functions analogous to those of basic principles of the internal labour law. A substantial number of conventions corresponding to some of those principles suggests a high degree of detailed regulation provided. In fact most of these conventions concern details which can find more circumstantial regulation in international law than it is done in internal labour law, especially in acts of legislation: A comparison of specific international and internal provisions relating to the same question can usually indicate that in the scope of their wording they are almost not different, especially in the respect of a possibility of their application in internal law. They are of a self-executing character which can be indirectly proved by the fact that some labour codes prescribe expressis verbis applying the ILO conventions in specific individual matters not being regulated by internal law. Wording of certain provisions of the ILO conventions can also suggest adopting a principle of laying down certain rights (or duties) directly for the benefit of employees (or employers) and of describing situations in which rights or obligations formulated in the convention are to be regulated in internal law or by other acts of domestic authorities or other subjects of internal law. Another legal and dogmatic argument for the proprio vigore effectiveness of a substantial part of the ILO conventions in the internal relations is also the fact of their en bloc' ratification by the special ratifying act of the Diet. It can be also proved by way of entering into an agreement adopted in Poland, ratification procedures and, especially a „qualified" mode provided for the ILO conventions. It is implied that internal law has to be brought to conform to the ILO regulations and conformity to socio-political conditions has to be examined before and not after ratification. Some opinions expressed in the doctrine of labour law ought to be rediscussed as it seems, in light of these findings; it concerns those views Which assume that provisions of the ILO conventions must be, as a rule, substantiated in internal laws. It has to be therefore postulated to regulate a relation of international to internal law in the Polish constitution. The relation of the ILO conventions to internal labour law can be additionally regulated in labour code, provided the participation of the Diet in the convention ratification process.
Effectiveness of the ILO conventions in Polish labor law